How do human values influence the beef preferences of consumer segments regarding animal welfare and environmentally friendly production?. (December 2018) - Sonoda, Yuta; Oishi, Kazato; Chomei, Yosuke; Hirooka, Hiroyuki
Abstract: Animal welfare and environmental impacts have been emphasized in the sustainable production of livestock. Labels are useful tools for clearly providing such attribute information to consumers. The aim of this study was to evaluate how human values influence consumer segments for beef with information on animal welfare and environmentally friendly production. Using a choice experiment, we examined whether animal welfare and environmentally friendly labels, country of origin and price impact consumer choice. As results, five heterogeneous consumer classes were identified using a latent class model: label conscious, domestic beef preferring, price conscious, animal welfare preferring and not interested in production method . Almost 90% of consumers were interested in and willing to pay for beef with animal welfare or environmentally friendly label. The classes with significant preferences for such labeled beef were affected by " openness to change ", " self-enhancement " and " security ". Improving consumer attitudes and strengthening consumer perception towards labeled beef by marketers and policy makers will be required. Highlights: The relations between human values and consumer preferences for beef were analyzed. Preferences for animal welfare and environmentally friendly labels were quantified. Five heterogeneous consumer segments were influenced by certain human values. The value "Security" positively affected the choice of labeled beef in Japan.